Type 1 interferon mediated signaling is indispensable for eliciting anti-tumor responses by Mycobacterium indicus pranii - Roy, Gargi; Chakraborty, Anush; Swami, Bharati; Pal, Lalit; Ahuja, Charvi; Basak, Soumen; Bhaskar, Sangeeta (Frontiers in Immunology, 2023)
The evolving tumor secretes various immunosuppressive factors that reprogram the tumor microenvironment (TME) to become immunologically cold. Consequently, various immunosuppressive cells like Tregs are recruited into the TME which in turn subverts the anti-tumor response of dendritic cells and T cells. Tumor immunotherapy is a popular means to rejuvenate the immunologically cold TME into hot. Mycobacterium indicus pranii (MIP) has shown strong immunomodulatory activity in different animal and human tumor models and has been approved for treatment of lung cancer (NSCLC) patients as an adjunct therapy. Previously, MIP has shown TLR2/9 mediated activation of antigen presenting cells/Th1 cells and their enhanced infiltration in mouse melanoma but the underlying mechanism by which it is modulating these immune cells is not yet known. This study reports for the first time that MIP immunotherapy involves type 1 interferon (IFN) signaling as one of the major signaling pathways to mediate the antitumor responses. Further, it was observed that MIP therapy significantly influenced frequency and activation of different subsets of T cells like regulatory T cells (Tregs) and CD8+ T cells in the TME. It reduces the migration of Tregs into the TME by suppressing the expression of CCL22, a Treg recruiting chemokine on DCs and this process is dependent on type 1 IFN. Simultaneously, in a type 1 IFN dependent pathway, it enhances the activation and effector function of the immunosuppressive tumor resident DCs which in turn effectively induce the proliferation and effector function of the CD8+ T cells.